An algorithmized system for optimizing diagnosis in patients with osteoarthrosis of large joints - Filipenko, Volodymyr; Leontyeva, Frieda; Tuliakov, Vladyslav; Makolinets, Kyrill (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The indices, which have the largest diagnostic sensitivity and informativity at different stages of the disease, were revealed on the basis of analysis of results of biochemical examinations of blood serum in 199 patients with osteoarthrosis of large joints. An algorithmized system, consisting of three blocks, was developed for assessing the course and correcting metabolic disturbances in osteoarthrosis of large joints. At the primary stage, the blood serum levels of sialic acids, seroglycoids and chondroitin sulphates are detected. The second block (additional examination) consists of studies of the levels of C-reactive protein and haptoglobin, protein fraction composition, hexoses of glycoproteins and glycosaminoglycans, activity of alkaline and acid phosphatases, excretion of glycosaminoglycans and hydroxyproline. Diagnosis is clarified with the third functional block, variant A, which includes revealing of rheumatoid factor and uric acid concentrations, antibodies to chlamydiae, ureaplasmas, mycoplasmas, gardnerellas. Variant B includes revealing of the content of hexosamines, protein-bound hexoses and aggrecan components (chondroitin-6-sulphate, chondroitin-4-sulphate and keratin sulphates).